HUBUNGAN PENGETAHUAN,SIKAP DAN PELAYANAN KB DENGAN KEIKUTSERTAAN PRIA DALAM PROGRAM KB DI KECAMATAN PANGURURAN KABUPATEN SAMOSIR TAHUN 2015 - Elsarika Damanik; Idaria Sidabuke; Lisa Hartini (UNIVERSITAS SARI MUTIARA INDONESIA, 2016)
The data from the Health Agency of Labuhanbatu in 2015 revealed that men’s participation in using KB (Family Planning) devices was still low, compared with that of woken. The proportion of men who participated in vasectomy KB acceptors in Labuhanbatu Regency was 1.37%. The objective of the research was to analyze some factors which were correlated with men’s participation on vasectomy KB. The researchwas an analytic survey with cross sectional design. It was conducted in Rantau Selatan Subdistrict, Labuhanbatu Regency, in May, 2016. The population was 6,784 men, and 261 of them were used as the samples. The data were analyzed by using univariate analysis, bivariate analysis with chi square test, and multivariate analysis with multiple logistic regression analysis. The result of the analysis showed that the factors whichwere correlated with men’s participation in vasectomy KB in Rantau Selatan Subdistrict, Labuhanbatu Regency, were knowledge (p=0.011) and attitude (p=0.006), while age (p=276), education (p=0.607), perception (p=0.117), wives’ support (p=0.388), health care providers’ support (p=0.335) were not. The variable which had the most dominant correlation was attitude at Exp (β)/OR = 19.214. It is recommended that health care providers provide health counseling or education for the people, especially married men who had children, about MOP contraception device so that their knowledge and attitude become better and they will be willing to become MOP KB acceptors.